Sonoelastography of the Plantar Fascia - Wu, Chueh-Hung; Chang, Ke-Vin; Mio, Sun; Chen, Wen-Shiang; Wang, Tyng-Guey (Radiology, 2011)
To compare the stiffness of the plantar fascia by using sonoelastography in healthy subjects of different ages, as well as patients with plantar fasciitis. The study protocol was approved by the Research Ethics Committee of the hospital, and all of the subjects gave their informed consent. Bilateral feet of 40 healthy subjects and 13 subjects with plantar fasciitis (fasciitis group) were examined by using color-coded sonoelastography. Healthy subjects were divided into younger (18-50 years) and older (> 50 years) groups. The color scheme was red (hard), green (medium stiffness), and blue (soft). The color histogram was subsequently analyzed. Each pixel of the image was separated into red, green, and blue components (color intensity range, 0-255). The color histogram then computed the mean intensity of each color component of the pixels within a standardized area. Mixed model for repeated measurements was used for comparison of the plantar fascia thickness and the intensity of the color components on sonoelastogram. Quantitative analysis of the color histogram revealed a significantly greater intensity of blue in older healthy subjects than in younger (94.5 ± 5.6 [± standard deviation] vs 90.0 ± 4.6, P = .002) subjects. The intensity of red and green was the same between younger and older healthy subjects (P = .68 and 0.12). The intensity of red was significantly greater in older healthy subjects than in the fasciitis group (147.8 ± 10.3 vs 133.7 ± 13.4, P < .001). The intensity of green and blue was the same between older healthy subjects and those in the fasciitis group (P = .33 and .71). Sonoelastography revealed that the plantar fascia softens with age and in subjects with plantar fasciitis.